A new intermediate in the Prins reaction - Yamabe, Shinichi; Fukuda, Takeshi; Yamazaki, Shoko (Beilstein Journal of Organic Chemistry, 2013)
Two Prins reactions were investigated by the use of DFT calculations. A model composed of R–CH=CH2 + H3O+(H2O)13 + (H2C=O)2, R = Me and Ph, was adopted to trace reaction paths. For both alkenes, the concerted path forming 1,3-diols was obtained as the rate determining step (TS1). TS stands for a transition state. From the 1,3-diol, a bimolecular elimination (TS2) leads to the allylic alcohol as the first channel. In the second channel, the 1,3-diol was converted via TS3 into an unprecedented hemiacetal intermediate, HO–CH2–O–CH(R)–CH2–CH2–OH. This intermediate undergoes ring closure (TS4), affording the 1,3-dioxane product. The intermediate is of almost the same stability as the product, and two species were suggested to be in a state of equilibrium. While the geometry of TS1 appears to be forwarded to that of a carbocation intermediate, the cation disappeared through the enlargement of the water cluster. Dynamical calculations of a classical trajectory using the atom-centered density matrix propagation molecular dynamics model on the four TSs were carried out, and results of IRC calculations were confirmed by them.
Keywords: DFT calculations; hemiacetal intermediate; hydrogen bond; Prins reaction; transition state